2010
DOI: 10.1111/j.1365-3156.2010.02676.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of risk factors and socio‐economic status in pulmonary tuberculosis: a search for the root cause in patients in a tertiary care hospital, South India

Abstract: Summaryobjective To determine the frequency of underlying risk factors and the socio-economic impact based on occupation in the development of tuberculosis. results Diabetes mellitus (DM) (30.9%) was the most prevalent condition and significantly more common than other risk factors like smoking (16.9%), alcoholism (12.6%), HIV (10.6%), malignancy (5.8%), chronic liver diseases (3.9%), history of contact with TB (3.4%), chronic corticosteroid therapy (2.9%), chronic kidney diseases and malnourishment (1.5%). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
41
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 11 publications
9
41
0
Order By: Relevance
“…In our study, 7.6% patients were HIV infected similar to this, Hill et al 13 and Gupta S et al 12 showed HIV prevalence of 6.1% and 10.6% in TB patients respectively in their studies. In our study, 10.2% patients had diabetes mellitus whereas study by Srivatava AB et al 14 …”
Section: Discussionsupporting
confidence: 89%
“…In our study, 7.6% patients were HIV infected similar to this, Hill et al 13 and Gupta S et al 12 showed HIV prevalence of 6.1% and 10.6% in TB patients respectively in their studies. In our study, 10.2% patients had diabetes mellitus whereas study by Srivatava AB et al 14 …”
Section: Discussionsupporting
confidence: 89%
“…15,16 In the present study, labourers were 37% and unemployed individuals (retired persons, students and housewives) were 33.4% in urban area but labourers were 49% and unemployed individuals (retired persons, students and housewives) were 19.4% in the rural area. This was very similar to the findings of Gupta et al, Khan, Muniyandi et al, Rajeswari et al and Gajbhare et al 4,5,15,25,27 A study by Schoeman et al argued that the role of socioeconomic status as a risk factor for TB was shown to be unclear but the study by Muniyandi et al reported that 61.75% cases belonged to Below Poverty Line (BPL). 25,28 In the present study, majority of the study participants were from middle and upper middle class in urban area and lower, middle, and upper middle class in rural area.…”
Section: Discussionsupporting
confidence: 85%
“…The middle age group had accounted for more than 60% of PTB both in urban and rural areas which were similar to the previous studies. 4,[17][18][19] It is noteworthy in the present study that 24.4% in urban area and 20.8% in rural area affected by PTB belonged to the age group of above 55 years. Since, in older age groups PTB might be present only as cough that could be ignored.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Balakrishnan et al 10 using glycosylated haemoglobin (HbA1c) as a diagnostic tool, reported DM prevalence of 44% among TB patients 10 . DM was found as the most frequent risk factor for pulmonary TB in another retrospective study from India 11 . Pakistan reported ten times higher prevalence of DM in TB patients compared to normal population 12 .…”
Section: Epidemiologymentioning
confidence: 85%